Pengembangan Instrumen Perencanaan Karir Sekolah Kejuruan - Hengka Nove, Albertus (Universitas Palangka Raya, 2024)
The aim of this research is to develop an instrument in the form of a career planning inventory for vocational school. There are 35 statement items developed based on 3 aspects of career planning, namely aspects of knowing yourself, exploring a career, and choosing a career. The research sample was 60 vocational students. There are 2 steps taken in developing the instrument, namely (1) to determine the readability of the instrument by involving career planning instrument experts and (2) to determine the level of validity and reliability of the instrument. Based on the readability of the instrument by experts, it was found that the instrument was in the relevant category for use. Then the validity test of the 35 statement items showed that 32 items were valid and 3 items were invalid. Furthermore, 32 statement items were tested for reliability, showing that the Cronbach's Alpha results were greater than the r table. So it can be concluded that the career planning instrument with 32 statement items is relevan,valid and reliable for use by vocational students in career planning.